تأثیر الاتصال الداخلي ودوره في تحسین الأداء البشري في المؤسسة الاقتصادیة دراسة حالة مؤسسة سوناطراك مركب G - مزیان , محمد توفیق (Finance and Business Economies Review, 2018)
The aim of this study is to identify the type of relationship between internal communication and improve human performance in the Sonatrach Foundation GL2Z. It also aims to identify the reality of the communication system in the institution. To achieve this purpose, we adopted the descriptive approach and the analytical approach to data analysis, The questionnaire was distributed to a sample of 88 individuals working at the institution. The study hypotheses were also processed and tested using the statistical package of social sciences (SPSS20), based on a set of statistical methods such as Cronbach alpha, arithmetic mean and standard deviation, Pearson correlation coefficient. After the analysis and analysis, the study reached a set of results that proved a strong positive relationship between the internal communication and the human performance in the institution. The study considered that the communication process requires a good and modern equipped system that keeps abreast of the tremendous developments in communications. The study also considered that the performance of the human element is the basis for improving the performance of the institution as a whole.